GOVERNMENT CONTRACTING promises and perils. - Curry, William Sims ([S.l.] : ROUTLEDGE, 2023)
Through three comprehensive editions, Government Contracting: Ethical Promises and Perils in Public Procurement has been lauded for exposing fraud, incompetence, waste, and abuse (FIWA) and analyzing corruption, mismanagement, and ineptitude that defile government contracting. The first two editions thoroughly outlined procurement throughout the contracting cycle including initial planning, evaluating proposals, contractor selection, contract administration, contract closeout, and auditing. They further provided much-needed guidance on contracting documents, management tools, and processes for addressing negative influences on government contracting. This third edition incorporates the results of a new nationwide study into best public procurement practice, as well as recent examples of real-world procurement fraud cases, offering recommendations for procurement practices to deter fraud. Public procurement tools such as requests for proposals, pro forma contracts, proposal evaluation forms, sole source justification and approval forms, and other useful tools including PowerPoint presentations are provided on a website to accompany the book. This textbook is aimed at postgraduate students and academics working in the fields of public administration, policy and procurement, along with public procurement professionals.
OCLC-licensed vendor bibliographic record.
Keywords: Government purchasing -- Law and legislation -- United States; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General; BUSINESS & ECONOMICS / Purchasing & Buying